A qualitative study on the clinical safety and user experiences of female condoms for anal intercourse among men who have sex with men in Shanghai, China - Huang, Jia-Lu; Xin, Xin; Ma, Ming-Jun; Ning, Zhen; Xiao, Shao-tan; Chen, Pan-pan (Frontiers in Public Health, 2023)
Objective: This qualitative study aims to understand the clinical safety, efficacy, and receptiveness of using the female condom(FC) during anal intercourse among (MSM). Methods: Subjects for this study were recruited from a two-group crossover trial among MSM in Shanghai. The trial consisted of two phases, each including the use of condoms (FC vs. male condom), questionnaires, and in-depth one-on-one interviews. The two phases were separated by a washout period of 4 weeks. The qualitative data were organized and analysed using Atlas.ti version 7. Results: A total of 26 participants from the MSM population were recruited for this study, with 10 assuming the insertive role (i.e.,"1"), 8 assuming the receptive role (i.e.,"0"), and 8 being versatile (i.e.,"0.5"). The cumulative usage of FC and male condoms (MC) amounted to 115 and 127 times, respectively. During the reported sexual encounters, no participants reported incidents of condom rupture, slippage, or other malfunctions. A few participants reported experiencing slight chafing pain, primarily put forwards by "0" participants. Apart from those reports, no instances of bleeding, swelling, or allergic reactions were reported. The efficiency of FC in disease prevention, sexual partner's willingness to use FC, the freshness of FC and positive sexual experiences were the main reasons for the consistent use of FC for anal sex. The elements referring to the forehead exhibited varied in importance among "1","0" and "0.5"participats. Regarding the willingness to use the FC in future anal intercourse, 61.54% of participants expressed a positive inclination, 23.08% were uncertain, and 15.38% stated that they would not. "A better sense of security during anal sex" was the main factor affecting willingness among "0" participants, and "the sexual pleasure that the FC brought" among "1" participants. Improving the design and technology of FCs and increasing the frequency of use and practice might improve the use skills, which will favour the willingnessto use FCs among the MSM population.FCs received positive user feedback from study participants,but distinctions were found individuals in different sexual roles. Large-scale quantitative studies are needed to evaluate the FC's clinical safety and effectiveness in preventing the transmission of STDs during anal intercourse.